2010
DOI: 10.1016/s1028-4559(10)60038-1
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Supplementation and the Incidence of Preeclampsia in Pregnant Iranian Women: A Randomized, Double-Blind, Placebo-Controlled Pilot Trial

Abstract: Our findings indicate that selenium supplementation in pregnant women may be associated with a lower frequency of preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 39 publications
1
23
0
3
Order By: Relevance
“…Dietary selenium intake or supplementation has been related to higher antioxidant enzymatic activity and lower lipid peroxidation. In contrast, selenium deficiency leads to a decline in tissue levels of selenium-dependent antioxidant enzymes and thereby oxidative stress conditions develop (9). Several authors have indicated that supplementation with n-3 LCPUFA enhanced oxidative stress at dietary intakes higher than that contained in the fish supplied in our study (the equivalent of about 500 mg/day).…”
mentioning
confidence: 56%
“…Dietary selenium intake or supplementation has been related to higher antioxidant enzymatic activity and lower lipid peroxidation. In contrast, selenium deficiency leads to a decline in tissue levels of selenium-dependent antioxidant enzymes and thereby oxidative stress conditions develop (9). Several authors have indicated that supplementation with n-3 LCPUFA enhanced oxidative stress at dietary intakes higher than that contained in the fish supplied in our study (the equivalent of about 500 mg/day).…”
mentioning
confidence: 56%
“…Placebo controlled clinical trials also increase the fertility of men living in low selenium areas leading to successful conception [71]. Dietary selenium also reduces pre-labor membrane rupture and preeclampsia [72,73]. …”
Section: Clinical Studies With Dietary Seleniummentioning
confidence: 99%
“…Limited trials have been conducted to test the effectiveness of selenium supplementation in preventing complications of pregnancy [39,40]. The recently published SPRINT (Se in PRegnancy INTervention) trial examined biochemical markers associated with the development of pre-eclampsia and found a significant reduction in soluble fms-like tyrosine kinase-1 (sFLT-1) in women treated with selenium [40].…”
Section: Discussionmentioning
confidence: 99%